District-level spatial analysis of migration flows in Ghana: Determinants and implications for policy - Daniel Tsegai; Quang Bao Le (University of Bonn, Center for Development Research (ZEF), 2010)
The present study investigates the determinants of inter-district migration flows over the 1995-2000 period in Ghana. A combination of socio-economic, natural and spatial district-level attributes are considered as potential variables explaining the direction of migration flows. In addition to the net migration model, in and out migration models are also employed within the context of the gravity model. Results in the three models consistently show that people move out of districts with less employment and choose districts with high employment rate as destinations. While shorter distance to roads encourages out-migration, districts with better water access seem to attract migrants. Generally, people move out of predominantly agrarian districts to relatively more urbanized districts.
Keywords: 330; Gross migration; Net migration; Inter-district migration flows; spatial analysis; Ghana; Africa; Binnenwanderung; Landflucht; Regionaler Arbeitsmarkt; Wasserversorgung; Ghana